2021
DOI: 10.1186/s13287-021-02493-5
|View full text |Cite
|
Sign up to set email alerts
|

Low level laser therapy promotes bone regeneration by coupling angiogenesis and osteogenesis

Abstract: Background Bone tissue engineering is a new concept bringing hope for the repair of large bone defects, which remains a major clinical challenge. The formation of vascularized bone is key for bone tissue engineering. Growth of specialized blood vessels termed type H is associated with bone formation. In vivo and in vitro studies have shown that low level laser therapy (LLLT) promotes angiogenesis, fracture healing, and osteogenic differentiation of stem cells by increasing reactive oxygen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 50 publications
3
44
0
Order By: Relevance
“…Recent studies suggest a photobiomodulation-induced coupling role of angiogenesis and osteogenesis, as well as related gene expression including HIF-1α and VEGF, both in vivo and in vitro. This evidence was derived from the observation of reactive oxygen species (ROS)-triggered increase in irradiated cells, which resulted in the subsequent crosstalk between angiogenesis and osteogenesis [29]. Our results also showed that photobiomodulation succeeded to simultaneously enhance both VEGF and OCN mRNA expression densities in diabetic tooth extraction sockets, proposing a latent mechanism of photobiomodulationmediated wound healing improvement in diabetic rats.…”
Section: Discussionsupporting
confidence: 61%
“…Recent studies suggest a photobiomodulation-induced coupling role of angiogenesis and osteogenesis, as well as related gene expression including HIF-1α and VEGF, both in vivo and in vitro. This evidence was derived from the observation of reactive oxygen species (ROS)-triggered increase in irradiated cells, which resulted in the subsequent crosstalk between angiogenesis and osteogenesis [29]. Our results also showed that photobiomodulation succeeded to simultaneously enhance both VEGF and OCN mRNA expression densities in diabetic tooth extraction sockets, proposing a latent mechanism of photobiomodulationmediated wound healing improvement in diabetic rats.…”
Section: Discussionsupporting
confidence: 61%
“…Simple bone fractures or defects can be repaired and recovered by the body itself, but in diabetic microenvironment, fractures tend to take a long time to repair, as the ability of the body is limited. [ 27 ] Thus, we examined hydrogel biomaterials for the acceleration of bone reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Through further investigation, it was found that these effects were induced through the ROS/ Hif-1α signaling pathway, emphasizing LLLT's production of ROS as the key feature in promoting angiogenesis and osteogenesis. While their results highlight the increase in ROS being beneficial to angiogenesis and osteogenesis, the study emphasizes a suitable window for osteogenic differentiation, with higher ROS levels damaging osteogenic differentiation at later timepoints (Bai et al, 2021).…”
Section: Other Bioengineering Techniques That Modulate Reactive Oxyge...mentioning
confidence: 95%
“…Rather than focusing on reducing ROS, others have acknowledged that an increase in ROS is necessary for osteogenesis, especially for the formation of blood vessels to adequately vascularize bone. Bai et al demonstrated the use of low-level laser therapy (LLLT) in promoting coupled angiogenesis and osteogenesis by use of a BMSC and biphasic calcium phosphate graft implanted into mice and an endothelial and bone marrow stem cell coculture (Bai et al, 2021). Both in vivo and in vitro studies demonstrated a significant increase in angiogenesis and osteogenesis as well as upregulation of VEGF, TGF-β, and Hif-1α.…”
Section: Other Bioengineering Techniques That Modulate Reactive Oxyge...mentioning
confidence: 99%